Upaya Meningkatkan Kepercayaan Diri Siswa Melalui Kegiatan Muhadharah - Arini Alfa Hidayah; Sri Tuti Rahmawati (Prodi Pendidikan Keagamaan Islam, 2024)
This article is motivated by the fact that there are still many students or teenagers who behave negatively, so it is necessary to preach and instill Islamic values in every student. However, in preaching, confidence is certainly needed from each individual, so this study will discuss the existence of one of the religious programs at school, namely muḥāḍharah activities, with the muḥāḍharah program being able to instill Islamic values in students and can develop their talents, interests and the process of creating their maturity of progress in the future, especially in terms of preaching and training them to be confident and responsible. This research aims to find out: (1) The implementation of muḥāḍharah activities at SMPI Nurul Hidayah Depok, and (2) What efforts are made to increase student confidence in muḥāḍharah activities. The research method used is a qualitative research method with a descriptive approach. Data collection techniques through observation, interviews, and documentation obtained directly from research in the form of notes, recordings, photos and data from sources related to the research. Data analysis techniques used are data collection, data reduction, and conclusions. The results show that muḥāḍharah activities are good enough to train the courage of speaking skills and increase students' confidence to perform in front of many people. This activity is carried out every Friday at 07.15-08.00 WIB which is attended by all students from class VII-IX. To increase students' confidence in muḥāḍharah activities by training and familiarizing students to play an active role in learning and including students in various competitions that are integrated with muḥāḍharah activities both in PHBI events, competitions between schools, districts or cities.